Need Assessment Dalam Menentukan Program Kursus Bahasa Inggris Oleh Pengelola Pada LKP Lantern House Kota Bengkulu - Sipsiansyah Sipsiansyah; Ilham Adbullah; Suardi Jasma (UNIB Press, Universitas Bengkulu, 2019)
The aim of this research is to know the identifiation of society learning needs by the manager of LKP Lantern House Bengkulu in determining an english cource program. The method of this research was used qualitative approach with descriptive data. The collection of data was used with three of techniques by interview, observation, and documentation. The data analyse of this research was used by three of ways by reducting data, displaying data, and taking a result and verification. The result of this research have indicated that : (1) The manager used steps of need assessment by collecting information, identifying for asymmetry, performance analyse, identifying for inhibiton and source, identifying for the student characteristic, identifying for the purpose, and determing the problem. (2) The manager used observation as the thecnique in identifying the society learning needs. (3) The method used by the manager in identifying the society learning needs were promotion and communication approach. (4) The manager did not used a special model of assessment in identifying the society learning needs. (5) In determining the priority program, the manager used his self assumption by analysing need assessment to english. (6) In process of identifying the society learning needs, the manager found the inhibition factors in the field as well as intern factor ( lack of partners and financial) and extern factor (less of finding location for promotion and observation). (7) The supporting factors in process of identifying the society learning needs were as intern factor (optimist and capable in using IT) and extern factor (partner relation with any organization or community). The recomendation of this research is given to all of the institutions or the manager that before offering the learning or cource program must to identify the society learning needs previoulsy the program is offered suitable of the society needs. Key Words : Need Assessment, English Cource Program, and The Manager of LKP